SCHOOL MARKS AND PROFESSIONAL INTEGRITY - Lucow, William H. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1968)
What professional savoir-faire can a teacher display when something unusual happens during an examination? Should marks be deducted from the scores of children who disobey the teacher, or talk, or disturb the class, or even cheat? Should the reduced score be entered in the official record, or should some other action be taken? Wherein lies professional duty?